Tokenization and Morphological Analysis for Malagasy - Dalrymple, M; Liakata, M; Mackie, L (CSLI Publications, 2019)
We present a tokenizer and finite-state morphological analyzer (Beesley and Karttunen, 2003) for Malagasy, based primarily on the discussion of Malagasy morphology in Keenan and Polinsky (2001) and Randriamasimanana (1986). Words in Malagasy are built from roots by means of a variety of morphological operations such as compounding, affixation, and reduplication. We analyze productive patterns of nominal and verbal morphology, describing genitive compounding and suffixa- tion for nouns, and various derivational processes involving compounding and affixation for verbs. Our work offers a computational analysis of Malagasy morphology, and forms the basis of our computational grammar and lexicon of Malagasy within the framework of the PARGRAM project.